(untitled) (Ustozlar uchun, 2025)
Lymphoma, a malignancy of the lymphatic system, often presents with diverse systemic symptoms, including notable ocular manifestations. This article explores the spectrum of eye changes associated with lymphoma, encompassing both primary ocular lymphomas and secondary involvement due to systemic disease. We discuss the pathophysiology, clinical features, diagnostic challenges, and therapeutic approaches relevant to ocular lymphoma. Understanding these changes is critical for timely diagnosis and appropriate management, which can significantly impact patient prognosis and quality of life.